Who decides? The governance of rewilding in Scotland 'between the cracks': community participation, public engagement, and partnerships. (February 2023) - Martin, Alison; Fischer, Anke; McMorran, Rob
Abstract: Rewilding is a conservation approach which seeks to restore natural processes and ecosystem functionality. However, it also has a strong social dimension, characterised by a recently increasing emphasis on the place of people in rewilding. The role of local communities and the need for public engagement have become a specific concern for many contemporary rewilding efforts. Research on the role of participation in rewilding is however lacking, with rewilding governance in general being under-explored. Our examination of understandings and practices of rewilding governance, through semi-structured interviews with key stakeholders in Scotland, illustrated a range of conceptualisations and approaches. It became apparent that governance and participatory practices were very variable and selective, highlighting an interaction between land ownership and degrees of empowerment which underpinned rewilding activity and decision-making. Approaches ranged from relatively ubiquitous advocacy for public engagement with a pre-prescribed rewilding agenda, through the circumscribed participation of defined communities (mainly of interest) in specific activities, to much more involved and empowering but self-selecting partnerships (with other landowners) to achieve impact at scale. Key challenges to more participatory approaches in rewilding identified included: i) a strong conservation imperative; ii) concentrated ownership, and power and control over land; and iii) emerging ideas about the public interest. These influenced perceptions about the value, and the practice of greater representation in rewilding decisions, ultimately bounding and limiting the participation of communities and the public. Highlights: Governance of rewilding in Scotland is diverse and takes place 'between the cracks'. Community and public engagement are seen as important, but practiced selectively. Conservation imperative and land ownership challenge more participatory practice. Meaningful participation requires engagement with divergent views.